Steps in Implementing the Evaluation of Islamic Religious Education (PAI) Learning - Abdurrasyid, Abdurrasyid; Panggabean, Hadi Saputra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Learning evaluation of Islamic Religious Education (PAI) is an important step to measure the effectiveness of the teaching and learning process. This study aims to identify the steps that need to be taken in conducting Islamic Education learning evaluation. Through literature review and data analysis, this study concludes that evaluation steps include planning, implementation, and follow-up. Planning includes determining objectives, selecting instruments, and scheduling the evaluation. Implementation includes collecting data through various techniques, such as written tests, observations, and interviews. Follow-up includes data analysis, interpretation of results, and preparation of recommendations for learning improvement.